2021
DOI: 10.1016/j.rser.2020.110562
|View full text |Cite
|
Sign up to set email alerts
|

Sources of inefficient power generation by coal-fired thermal power plants in China: A metafrontier DEA decomposition approach

Abstract: China is the world's largest CO2 emitting country and coal-fired thermal power generation accounted for over 50% of total electricity generation in China in 2015. This study reports the changes in power generation efficiency of coal-fired thermal power plants in China from 2009 to 2011 and how the differences in the production scale of the power plants and regional heterogeneity affect the power generation efficiency. We propose a metafrontier data envelopment analysis (DEA) decomposition framework to investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(50 citation statements)
references
References 39 publications
1
49
0
Order By: Relevance
“…Hu and Wang [20] (1) Capital; (2) Labor; (3) Energy consumption; (4) Total sown area of farm crops GDP Hu and Kao [23] (1) Capital; (2) Labor; (3) Energy consumption GDP Zhang et al [36] (1) Capital;(2) Labor;(3) Energy consumption GDP Song et al [37] (1) Capital formulation; (2) Labor; (3) Energy consumption GDP Lin and Du [38] (1) Capital; (2) Labor; (3) Energy consumption GDP Bian et al [39] (1) Capital; (2) Labor; (3) Energy consumption GDP Borozan [40] (1) Capital; (2) Employment; (3) Energy consumption GDP Jebali et al [41] (1) Capital; (2) Labor; (3) Energy consumption GDP Eguchi et al [42] (1) Capital; (2) Coal consumption (1) Net electricity production; (2) sample size Haider et al [43] (1) Capital; (2) Labor; (3) Energy consumption; (4) Material output Table A2. Cont.…”
Section: Tfee Without Pollutionmentioning
confidence: 99%
“…Hu and Wang [20] (1) Capital; (2) Labor; (3) Energy consumption; (4) Total sown area of farm crops GDP Hu and Kao [23] (1) Capital; (2) Labor; (3) Energy consumption GDP Zhang et al [36] (1) Capital;(2) Labor;(3) Energy consumption GDP Song et al [37] (1) Capital formulation; (2) Labor; (3) Energy consumption GDP Lin and Du [38] (1) Capital; (2) Labor; (3) Energy consumption GDP Bian et al [39] (1) Capital; (2) Labor; (3) Energy consumption GDP Borozan [40] (1) Capital; (2) Employment; (3) Energy consumption GDP Jebali et al [41] (1) Capital; (2) Labor; (3) Energy consumption GDP Eguchi et al [42] (1) Capital; (2) Coal consumption (1) Net electricity production; (2) sample size Haider et al [43] (1) Capital; (2) Labor; (3) Energy consumption; (4) Material output Table A2. Cont.…”
Section: Tfee Without Pollutionmentioning
confidence: 99%
“…China and the world have made great efforts to implement the green and low-carbon concepts of the Paris Agreement [9][10][11], focusing on themes such as thermal power generation and TPGU. China remains the world's largest emitter of carbon dioxide, mainly due to the high proportion of coal-fired thermal power [12,13]. The flexibility of TPGU [14][15][16][17], SO 2 emissions [18] and other indicators can only be used as a kind of technical indicators or TPGU improvement targets, which cannot be used to comprehensively evaluate TPGU.…”
Section: Introductionmentioning
confidence: 99%
“…DEA can estimate the efficiency of numerous decision‐making units (DMUs) simultaneously by considering multiple input and output factors and provide useful information for efficiency improvement (Charnes et al, 1978; Cooper et al, 2007). Sueyoshi et al (2017) reviewed a variety of previous studies in the environmental and energy fields and concluded that DEA has contributed to solving many environmental and energy issues by demonstrating the relationship between technological improvement in enterprise and industry and environmental issues (Eguchi et al, 2021; Emrouznejad & Yang, 2017; Sueyoshi & Goto, 2017). DEA is a frontier analysis, and the performance of a DMU is evaluated according to its relative distance to the frontier line enveloped by a reference set (i.e., best practice frontier).…”
Section: Introductionmentioning
confidence: 99%